Electromagnetic weak turbulence theory revisited - Yoon, Peter H. (2012)
The statistical mechanical reformulation of weak turbulence theory for unmagnetized plasmas including fully electromagnetic effects was carried out by Yoon [Phys. Plasmas 13, 022302 (2006)]. However, the wave kinetic equation for the transverse wave ignores the nonlinear threewave interaction that involves two transverse waves and a Langmuir wave, the incoherent analogue of the so-called Raman scattering process, which may account for the third and higher-harmonic plasma emissions. The present paper extends the previous formalism by including such a term.